The psycholinguistic factors affecting EFL students classroom interaction - Chaa, Imane (My University, 2017)
This study examines the psycholinguistic factors affecting EFL students classroom interaction. The present work is an endeavour to identify some obstacles behind EFL classroom interaction lack. The hypothesis adopted in this study sets out that if EFL teachers take into consideration the students’ psychological aspects and the linguistic background while teaching oral expression, classroom interaction will be promoted. The research method adopted for this piece of work was purely descriptive. The required data were gathered through questionnaires administered to L1 students of English, as well as their teachers at Abdelhamid Ibn Badis Mostaganem University. The results obtained have shown that psycholinguistic factors affect to some extent EFL students classroom interaction. On the light of these results, the earlier stated hypothesis was successfully confirmed in that promoting classroom interaction basically need to be accompanied with interaction activities which reinforces the students’sense of belonging ,reduce speaking problems and improve their oral proficiency. On the basis of the results obtained, this conducted research is not useful solely for students in helping them identifing their speaking difficulties, rather; it helps teachers as well in their understanding of the students’ psychological and linguistic backgroud impact on classroom interaction in order to promote interaction in their EFL classses.
Case study: L1 students of English at Abdelhamid Ibn Badis Mostaganem University
Keywords: EFL classrooms; Students interaction; Psychological role and impact